G486 Airway and alveolar nitric oxide production, lung function and pulmonary blood flow in sickle cell disease. (27th April 2016) - Lunt, A; Ahmed, N; Rafferty, GF; Dick, M; Rees, D; Height, S; Thein, SL; Greenough, A
Abstract : Aims: Children with sickle cell disease (SCD) often have obstructive lung function abnormalities. Those abnormalities could be due to asthma, but there is conflicting evidence regarding whether asthma is more common in SCD children. Another explanation for the airways obstruction is the increased pulmonary blood volume resulting from chronic anaemia in SCD patients. In asthmatics, exhaled nitric oxide (FeNO ) is elevated. FeNO, however, can also be raised due to increased alveolar production. Our aim, therefore, was to determine if airway or alveolar NO production differed between SCD children and ethnic and age matched controls. Such data would inform the debate as to whether airways obstruction in SCD is due to asthma or not and hence inform treatment strategies. Methods: African or Caribbean children with SCD (homozygous for sickle cell haemoglobin (HbSS)) and ethnic and age matched controls were recruited. Exhaled nitric oxide was measured at multiple flow rates to derive the total maximal airway NO flux and the alveolar NO concentration using a two-compartment model. The transfer factor for nitric oxide (DLNO) was measured using the single-breath method and used withthe alveolar NO concentration to derive the rate of alveolar NO production. The respiratory system resistance (Rrs) was measured using impulse oscillometry and a frequency of 5 Hz was used to assess small airway function. Lung function was also assessed by spirometry and static lung volumes and the transfer factor for carbon monoxide were measured. All results were expressed as the percent predicted for height. Results: The 18 SCD children compared to the 18 controls had a higher respiratory system resistance (p = 0.0008), alveolar NO production (p = 0.0224) and pulmonary blood flow (p < 0.0001), but not airway NO flux. There was no significant correlation between FeNO and respiratory system resistance in either group, but in the SCD children there were correlations between pulmonary blood volume and both alveolar NO production (p = 0.0006) and concentration (p < 0.0001). Conclusions: Airway NO flux was not elevated in the SCD children nor correlated with airways obstruction, suggesting that airways obstruction, at least in some SCD children, is not due to asthma.